Organizational systems managing complexity with the viable system model - Espejo, Raul.; Reyes, Alfonso; SpringerLink (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book clarifies the application of cybernetic ideas, particularly those of Beer's Viable System Model, to organizational diagnosis and design. Readers learn to appreciate the relevance of seeing the systemic coherence of the world. The book argues that many of the problems we experience today are routed in our practice of fragmenting that that needs to be connected as a whole. It offers a method to study and design organizations and a methodology to deal with implementation problems. It is the outcome of many years of working experience with government offices as well as with all kinds of public and private enterprises. At a more detailed level this book offers an in depth discussion of variety engineering that is not available either in the primary or secondary literature.
Electronic reproduction.
Keywords: Management information systems; Industrial organization; Organizational behavior; Electronic books